REMOTE VIRTUAL THE DATA STORAGE - Gustriansyah, Rendra (Institute of Research and Community Outreach - Petra Christian University, 2006)
Almost all computer users know Windows Explorer. With the windows explorer, a user could do the operation file/directory, such as seeing the structure of the hierarchy from the directory, copied some files et cetera. In other words, a window explorer had file manager facilities. This research will discuss the development of the application of the data storage based on web that had file manager facilities (remote virtual the data storage) with the previleges. This research could be applied for the management of the lectures data in the class or in the computer laboratory of a institution. Abstract in Bahasa Indonesia : Hampir setiap pengguna komputer mengenal Windows Explorer. Karena dengan Windows Explorer, user dapat melakukan operasi file/direktori, seperti melihat struktur hirarki dari direktori, menyalin file dan lain sebagainya. Dengan kata lain, window explorer memiliki fasilitas pengaturan file (file manager). Penelitian ini akan membahas pembangunan aplikasi penyimpanan data berbasis web yang mempunyai fasilitas pengaturan file (remote virtual the data storage) dengan hak akses yang berbeda (previleges). Penelitian ini dapat diimplementasikan untuk manajemen data perkuliahan di kelas maupun di laboratorium komputer suatu perguruan tinggi. Kata kunci: remote virtual the data storage, file manager, web, NAS.